Cranial anatomy and neuroanatomical features of a new specimen of Geosaurini (Crocodylomorpha: Metriorhynchidae) from west-central Argentina - Herrera, Laura Yanina (2014)
Fossil records of Geosaurini taxa in South American margins of the Eastern Pacific are scarce. We describe a new specimen of Geosaurini found in sedimentites of the Vaca Muerta Formation (Substeueroceras koeneni Biozone, uppermost Tithonian-lowermost Berriasian) and referred it as Dakosaurus cf. D. andiniensis. The close stratigraphic association of this specimen with late Tithonian to early Berriasian ammonoids allows confirming with biostratigraphic accuracy that, up to date, the first known occurrence of the Geosaurini taxa in South American is in late Tithonian. The specimen consists of a partially preserved skull and a partially exposed natural endocast of the brain cavity, which is the first detailed description of a natural endocast of a metriorhynchid. The conspicuous blood vessel fillings covering almost all the dorsal surface of the cerebral hemispheres suggest that the dural envelope of this region was thin and that the cerebral hemispheres filled most of the cavity. A large dorsal venous sinus that overlays the dorsal region of the hindbrain, a tube-like cavity connecting the cranioquadrate passage and an enlarged internal carotid canal, previously described for "Metriorhynchus" cf. "M." westermanni and present in Dakosaurus cf. D. andiniensis, suggest that these features were more widely distributed within metriorhynchids.